1970
DOI: 10.1126/science.169.3951.1208
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate: Feeding of Large Amounts in Man and Gerbils

Abstract: Oral administration of large amounts of glutamic acid to adult humans and animals in a formula diet appeared to cause no clinical pathological changes. The only biochemically demonstrable effect was a decrease in serum cholesterol and associated beta lipoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
1
3

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 9 publications
7
11
1
3
Order By: Relevance
“…We propose that this lowered serum cholesterol in conjunction with the lowered serum LH was responsible for the lowered serum testosterone levels recorded in this study. The significantly lower serum cholesterol recorded for goats given MSG in this present study is in agreement with the reports of Bazzano et al (1970) in humans and gerbils. However, Ahluwalia and Malik (1989) reported no effects on serum cholesterol in mice given MSG for six days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We propose that this lowered serum cholesterol in conjunction with the lowered serum LH was responsible for the lowered serum testosterone levels recorded in this study. The significantly lower serum cholesterol recorded for goats given MSG in this present study is in agreement with the reports of Bazzano et al (1970) in humans and gerbils. However, Ahluwalia and Malik (1989) reported no effects on serum cholesterol in mice given MSG for six days.…”
Section: Discussionsupporting
confidence: 93%
“…However, Ahluwalia and Malik (1989) reported no effects on serum cholesterol in mice given MSG for six days. The lowering of serum cholesterol by MSG administration in this study may be attributable to the reported destructive effects of MSG on the arcuate nucleus of the hypothalamus, which is known to partly function in regulation of fat metabolism (Bazzano et al 1970;Ahluwalia and Malik 1989;Dieguez et al 2011).…”
Section: Discussionmentioning
confidence: 74%
“…The significant lowering of the serum total cholesterol by MSG administration on Day 28 in this present study is corroborated by the reports of Bazzano et al (1970), Ochiogu et al (2015a) and Ochiogu et al (2015b) on studies with gerbils, rats and goats, respectively. However, it is not clear what effect this lowering of serum cholesterol exerted on testosterone concentrations in this study, as it is known that cholesterol is a precursor for testosterone biosynthesis (Hinshelwood 1998).…”
Section: Discussionsupporting
confidence: 80%
“…This lowered serum cholesterol is believed to be partly responsible for the significantly lower serum testosterone recorded for the MSG-treated rats, as testosterone is one of the steroid hormones synthesised from cholesterol (Stocco, 1998;Hu et al, 2010). The significantly lower serum cholesterol recorded for rats given MSG in this study is in agreement with the report of Bazzano et al (1970) on humans and gerbils, but contrasts with the reports of Ahluwalia and Malik (1989) and Inyang et al (2012).…”
Section: Discussioncontrasting
confidence: 56%